2007
DOI: 10.1177/039463200702001s15
|View full text |Cite
|
Sign up to set email alerts
|

SEM Analysis of Oral Lichen Planus before and after Treatment with 13 Cis-Retinoic Acid

Abstract: patients suffering from lichen planus and 20 control patients with healthy oral mucous were selected, From the case histories, of the patients suffering from lichen a good ability to modulate the inflammation and the locoregional immune response. In the case of severe symptoms, the association of systemic steroids may be indicated in the initial phase of the treatment (18).The association of antimicrobes improves the clinical results as it eliminates the proliferation C. Albicansand prevents eventual infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Mastrangelo, et al has also successfully shown improvement in the clinical and microscopic quality of epithelium with 13 cis RA by viewing and comparing pre and post treatment tissue samples under SEM. He also mentioned the role of RA in reversal of pathological state through morphostructural assessment of keratinocyte though relapse was common phenomenon present in both the studies [57].…”
Section: Deficiency Of Vitamin a Favors Reprogramming Of Treg Cellsmentioning
confidence: 99%
“…Mastrangelo, et al has also successfully shown improvement in the clinical and microscopic quality of epithelium with 13 cis RA by viewing and comparing pre and post treatment tissue samples under SEM. He also mentioned the role of RA in reversal of pathological state through morphostructural assessment of keratinocyte though relapse was common phenomenon present in both the studies [57].…”
Section: Deficiency Of Vitamin a Favors Reprogramming Of Treg Cellsmentioning
confidence: 99%